The Effect Of Giving Marmet Techniques On The Fluency Of Breastfeeding In Postpartum Mothers At The Gaji Health Center In 2023 (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2023)
Breastfeeding should be a pleasant experience for both mother and baby because there are many benefits of breastfeeding, including exclusive breastfeeding. But sometimes, various problems arise when breastfeeding both the mother and the baby, which complicates the process. The breastfeeding problems that may be experienced by the mother and the baby are; The problem is because the milk production is less so it does not provide exclusive breastfeeding. The purpose of this research is to find out "The Effect of Giving Marmet Techniques on the Smoothness of Breastfeeding for Postpartum Mothers at the Gaji Health Center in Tuban Regency".The research design used a pre-experimental type of design using a statistical test with a paired T test with a p value